Distribution of mast cells in the feline ovary in various phases of the oestrous cycle. (17th February 2017) - Hamouzova, P; Cizek, P; Novotny, R; Bartoskova, A; Tichy, F
Contents: This study is the first description of the distribution of mast cells in various phases of the oestrous cycle in the ovary of cat. Furthermore, this is the first description in species with an induced ovulation. The aim was to describe the distribution of mast cells and variability of their numbers in the feline ovaries in different phases of the oestrous cycle. The number of mast cells in medulla ovarii was affected by the estradiol and progesterone level in the blood serum because the lowest number was detected in anoestrus when the levels of hormones were basal. Nevertheless, both high and low numbers of mast cells were found in oestrus and dioestrus. To conclude, mast cells seem to be essential for the induction of spontaneous ovulation, but they do not play the same role for ovulation itself in cats with induced ovulation.